Long-term combined exercises enhance sweet taste sensitivity and reduce carbohydrate intake in patients with type 2 diabetes mellitus - Vidanage, Dinithi; Wasalathanthri, Sudharshani; Hettiarachchi, Priyadarshika (Asian Journal of Medical Sciences, 2022)
Background: The link between sweet taste perception and carbohydrate intake in diabetics who perform regular combined exercises has not been explored. Aims and Objectives: This study aimed at determining the impact of combined exercises on taste perception for sucrose and carbohydrate intake in patients with type 2 diabetes mellitus. Materials and Methods: A clinical trial was conducted with 225 patients with T2DM, aged 35–60 years assigned randomly into three groups; aerobic, combined, and a control group. Outcomes of the aerobic group were not reported. Combined group performed brisk walking 4–5 days/week and resistance exercises 2–3 days/week for 6 months. Supra-threshold intensity ratings, preference for sucrose, and carbohydrate intake assessed at baseline, at 3 and 6 months were measured using “general Labeled Magnitude Scale,” “Monell 2-series-forced choice method,” and a 3-day diet diary, respectively. Results: Ratings for the highest (combined vs. control: +3.15±0.57 vs. −7.96±0.40 mol/L, P=0.022) and the second-highest sucrose concentrations (combined vs. control: +7.79±4.49 vs. −8.98±0.99 mol/L, P=0.003) in the combined group were significantly higher with significant time × group interaction (2.02M: P=0.002, 0.64M: P=0.003). Preference for sucrose was lower in the combined group (combined vs. control: −0.08±0.14 vs. +0.01±0.03 mol/L, P=0.002), and the time × group interaction was not significant. Carbohydrate intake (combined vs. control: −46.97±21.60 vs. −6.30±9.36 g, P=0.001) and HbA1c level (combined vs. control: −0.66±1.81 vs. +0.33±1.84%, P=0.008) were reduced in the combined group, and taste sensitivity significantly predicted the carbohydrate intake with combined exercises (R2=0.64, P=0.01). Conclusion: Regular combined exercises increase sweet taste sensitivity for higher concentrations of sucrose. Taste sensitivity, not the preference determines the carbohydrate intake in exercising diabetics.